Perspektif Shariah Enterprise Theory: Penerapan PSAK 109 Pada Lazismu Lamongan - Evi Dwi Kartikasari; Muhammad Dzikri Abadi; Eka Prastia Pandu Asmara Dina Erlangga; Eli Indria (Journal on Education, 2022)
The aim of the research is to determine the level of conformity of accounting implementation regarding recognition, measurement, presentation and disclosure of Zakat and Infaq/Shadaqah financial reports with PSAK No. 109 and what is the Shariah Enterprise Theory (SET) perspective in Lazismu Lamongan. This type of qualitative research uses primary data in the form of interviews with informants and secondary data, namely financial reports. The analysis technique follows the recommendations of Miles and Huberman (1984), namely data collection then data reduction and data display then conclusion. The research results inform that Lazismu Lamongan's financial reporting is in accordance with PSAK 109, in terms of presenting Lazismu Lamongan using the format from the Center. The Shariah Enterprise Theory (SET) perspective as a whole is reflected in the activities carried out by Lazismu as stated in its annual reporting.